RISK FACTORS ASSOCIATED WITH BREAST CANCER IN ADULT WOMEN - Alejandro Arévalo, Olivia Francisca (2024)
Introduction: Breast cancer is one of the most prevalent malignant diseases with the greatest complications worldwide, representing a challenge for public health and women's well-being. Therefore, it is important to know the risk factors that can increase the probability of its development. Objective: Analyze the available scientific evidence related to the risk factors associated with breast cancer. Methods: Regarding the methodological framework, the guidelines of the Joanna Briggs Institute were followed and adapted to PRISMA ScR, the search was carried out in the databases: Pubmed, Scopus, as well as in the electronic repository: Scielo and the bibliographic search engine Google academic; it was also used for gray literature. The selection of evidence was carried out using Rayyan software, the extracted information was analyzed using a quantitative and qualitative approach. Results: 16 studies on modifiable risk factors were identified, in which: obesity, unhealthy diet, use of oral contraceptives, toxic habits (such as smoking and drinking alcohol) and certain aspects of anthropometry were found; Likewise, these studies showed non-modifiable factors such as: age, nulliparity, family history, sexual hormones and late menopause. Conclusions: Through prevention and education about these factors, we can significantly contribute to the reduction of complications of the disease and reduce its incidence, to improve the general well-being of women.